2019
DOI: 10.1021/acs.jpcb.9b01928
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Dipole Relaxation Processes in Water–Lysine Mixtures

Abstract: Dielectric spectroscopy is a robust method to investigate relaxations of molecular dipoles. It is particularly useful for studies of biological solutions because of the potential of this method to cover a broad range of dynamical time scales typical for such systems. However, this technique does not provide any information about the nature of the molecular motions, which leads to a certain underemployment of dielectric spectroscopy for gaining microscopic understanding of material properties. For such detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Molecular simulations on smaller 1-and 4-lysine molecules have shown that no aggregation is observed at high pH values. 49,50 These facts strongly suggest that the origin of the A-DLS cannot be due to concentration fluctuations. Additionally, a process observed by dynamic light scattering with the same phenomenological behaviour as observed here for e-PLL, has previously been found for other aqueous solutions (such as water mixtures of xylitol, 43 glucose, 51 or a-cyclodextrin 52 ).…”
Section: A-dls Processmentioning
confidence: 90%
“…Molecular simulations on smaller 1-and 4-lysine molecules have shown that no aggregation is observed at high pH values. 49,50 These facts strongly suggest that the origin of the A-DLS cannot be due to concentration fluctuations. Additionally, a process observed by dynamic light scattering with the same phenomenological behaviour as observed here for e-PLL, has previously been found for other aqueous solutions (such as water mixtures of xylitol, 43 glucose, 51 or a-cyclodextrin 52 ).…”
Section: A-dls Processmentioning
confidence: 90%
“…The electrical and dielectric properties of matter can be fully described by the complex dielectric permittivity function ε=εiε (or, since σ=iωε0ε, by the complex conductivity function σ=σ+iσ) 1 . The spectral and temperature dependence of ε directly reveal phenomena taking place at the molecular scale such as for instance dipolar relaxation processes 24 , phase transitions 57 and charge transport processes. 813 The direct correlation existing between the spectral dependence of ε and molecular phenomena is drastically impacted by the presence of interfaces and interphases, when the materials under study are heterogeneous (composite materials, multiphase materials, etc.).…”
Section: Introductionmentioning
confidence: 99%